João de Sousa Carvalho, Luciano Xavier dos Santos, José Joaquim dos Santos: Obras sacras, dir. Manuel Morais. João de Sousa Carvalho: Vésperas de Nossa Senhora, dir. Olivier Schneebeli - Cabral, Rui (Revista Portuguesa de Musicologia, 2014)
Recensão: João de Sousa Carvalho, Luciano Xavier dos Santos, José Joaquim dos Santos: Obras sacras, dir. Manuel Morais. João de Sousa Carvalho: Vésperas de Nossa Senhora, dir. Olivier Schneebeli